Pola Makan Sesuai Anjuran Nabi Muhammad SAW Menurut Perspektif Kesehatan - Fauzan Irfan; Nasywa Rahman; Siti Fatimah Azzahra; Gt. Muhammad Irhamna Husin (Pusat Riset dan Inovasi Nasional, 2023)
A healthy diet is the behavior of consuming food with balanced nutrition in sufficient quantities and not excessively. During his lifetime, Rasulullah Saw. as a role model in life for all Muslims in the world, he has taught many things, one of which is a healthy diet. This research was conducted as a means of reviewing the eating patterns of the Prophet Muhammad from a human health perspective, the nutrients contained in each food ingredient, as well as reviewing what the eating habits of the Prophet Muhammad as an Indonesian still carried out in public life. The method used in this research is qualitative research with a literature review.